Behind bars and bargains: New findings on transitional justice in emerging democracies - Dancy, G; Marchesi, B; Olsen, T; Payne, L; Reiter, A; Sikkink, K (Oxford University Press, 2019)
The global transitional justice tool kit—involving the use of criminal prosecutions, amnesties, and other mechanisms to address past human rights abuse—has become a primary means for thwarting future human rights violations and consolidating democracy. Nevertheless, evidence on the consequences of transitional justice remains mixed and amenable to contradictory interpretations. Existing studies fail to adequately address issues of selection, the difference between short- and long-term effects of transitional justice mechanisms, and qualitative and quantitative differences in state practices. This article uses a new database of transitional justice mechanisms to address these concerns and test propositions from realist, constructivist, and holistic approaches to this set of policy issues. We find, among other things, that prosecutions increase physical integrity protections, while amnesties increase the protection of civil and political rights. Our analysis suggests that different transnational justice policies each play a potentially positive, but distinct, role in new democracies and in decreasing violations of human rights.